2021
DOI: 10.1007/s00216-021-03326-3
|View full text |Cite
|
Sign up to set email alerts
|

Which particles to select, and if yes, how many?

Abstract: Micro- and nanoplastic contamination is becoming a growing concern for environmental protection and food safety. Therefore, analytical techniques need to produce reliable quantification to ensure proper risk assessment. Raman microspectroscopy (RM) offers identification of single particles, but to ensure that the results are reliable, a certain number of particles has to be analyzed. For larger MP, all particles on the Raman filter can be detected, errors can be quantified, and the minimal sample size can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…We believe that Raman-DOSY may find applications in the biomedical field to analyze the sizes of proteins in physiological solutions. Another application could be in the polymer research field , because polymers have narrow and intense Raman peaks in the fingerprint region and intense CH-stretch vibrations of the polymer backbone in the Raman spectra. We think that Raman-DOSY can be a useful complement to NMR-DOSY: it is comparatively cost-effective, does not require deuterated solvents, and opens up the possibility of analyzing samples that are difficult to measure with NMR, such as paramagnetic compounds or compounds that have strongly overlapping NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that Raman-DOSY may find applications in the biomedical field to analyze the sizes of proteins in physiological solutions. Another application could be in the polymer research field , because polymers have narrow and intense Raman peaks in the fingerprint region and intense CH-stretch vibrations of the polymer backbone in the Raman spectra. We think that Raman-DOSY can be a useful complement to NMR-DOSY: it is comparatively cost-effective, does not require deuterated solvents, and opens up the possibility of analyzing samples that are difficult to measure with NMR, such as paramagnetic compounds or compounds that have strongly overlapping NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance diffusion-ordered spectroscopy (NMR-DOSY) successfully combines the size sensitivity of the diffusion coefficient with the structural sensitivity of molecular spectroscopy and is a widely used technique to simultaneously determine the size and chemical structure of molecules. Here, we present the Raman analogue of this method. Raman spectroscopy is an excellent tool for analyzing the bond vibrations within a molecule, making it possible to identify a wide range of compounds with a high degree of certainty. The label-free nature of the method allows us to study the compounds in their native form and dissolved in aqueous solutions. However, the Raman spectrum generally provides little information about the size of molecules or aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the individual needs presented in Table 1 were derived from the AMAP Monitoring Guidelines (AMAP, 2021). To reduce the demand and costs for the chemical identification of microplastics, the approach of subsampling is commonly applied in microplastic research (Mintenig et al, 2020, Thaysen et al, 2020, Schwaferts et al, 2021. Depending on the type of spectroscopy applied, this can be performed via a minimum number of randomly selected particles or small fields of views which follow a random or specialized pattern by the instrumentation.…”
Section: Balancing Cost and Timementioning
confidence: 99%
“…Currently researchers have not agreed on an optimal strategy. While Mintenig et al (2020) found that 66% of the filter should be analysed using imaging techniques, other studies suggested to use different shapes or a defined number of a small fields (Brandt et al, 2021, Schwaferts et al, 2021. In the context of monitoring, either of these approaches is considered sufficient for determining the total number of plastic particles in a sample.…”
Section: Balancing Cost and Timementioning
confidence: 99%
“…In contrast, smaller particles might not all be detected on the entire filter, demanding a window-based analysis. For this purpose, a bootstrap method has been recently proposed by Schwaferts et al [95] to provide an error quantification with confidence intervals from the available window data. In this context, different window selection schemes have been evaluated and there is a clear recommendation to employ random (rather than systematically placed) window locations with many small rather than few larger windows.…”
Section: Models For Sub-sampling Of Particles Deposited On a Filtermentioning
confidence: 99%